Fruit and vegetable consumption among young school children in Pokhara, Kaski: A cross-sectional study - Shrestha, Nirmala; Banstola, Sanju; Sharma, Bimala (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Low intake of fruit and vegetable (F&V) increased the risk of non-communicable diseases, followed by disability and death. The fact that many diseases in adulthood have their origins in habits formed during childhood is undeniable. Therefore, the study assessed the prevalence of fruit and vegetable consumption among young schoolchildren aged 5 to 9 years. Methods: A cross-sectional study was carried out among 352 children from March 8 to September 4, 2020. The multistage sampling method was used to select samples. A face-to-face interview was done with one of the parents at their home. Univariate and bivariate analyses were computed at a 5% level of significance. Ethical approval was obtained from the Nepal Health Research Council. Results: Out of 352 children, none of the children met the WHO recommendation of F&V of ≥5 servings per day. Around two percentage (2.30%) of children consumed neither fruits nor vegetables, while only 46(13%) had taken F&V at least three servings per day. Children’s higher F&V intake was found to be associated with family monthly income, parents’ higher education, the presence of a fruit and vegetable shop nearby, and giving money to children. Conclusions: Intake of F&V as compared to the recommendation was very low in the study area. This requires an immediate response including nutrition education for parents, teachers, and decision-makers and increasing easy access to F&V.